COMPARISON OF SEVERAL METHODS FOR PARETO SET GENERATION IN MULTI-CRITERIA PORTFOLIO OPTIMIZATION - Radziukyniene, Ingrida; Žilinskas, Antanas (International Journal of Computing, 2014)
Pareto set generation methods are considered with respect to their application for multi criteria portfolio selection. Several such methods were compared experimentally including some recently proposed evolutionary methods and the method of adjustable weights. Test problems were based on standard portfolio quality criteria and data on stocks of 10 Lithuanian companies. The experimental data on the performance of the considered algorithms in different metrics are presented and discussed.